Synthesis and characterization of phenylene-based dicationic ionic liquids / Munirah Sufiyah Abd Rahim - Abd Rahim, Munirah Sufiyah (2012)

(untitled)
Dicationic ionic liquids are being developed and are found to have better properties than common room temperature ionic liquids. By comparison, they posses higher melting temperature, wider electrochemical window and stronger ion conductivity rather than RTILs. Previous reports suggest that dicationic ionic liquids have potential applications as solvent in organic synthesis, dye sensitized solar cells, phase transfer catalyst, lubricants, surfactants and as a stationary phase in gas liquids chromatography column. Eight series of dicationic ionic liquids were successfully synthesized by reacting α,α-dibromo-p-xylene with tertiary amines (pyridine, 1-methylpyrrolidine, 1-butylpyrrolidine, triethylamine, 1- methylpiperidine, 1-methylmorphline, N,N-dimethylethanoamine and N,Ndiethylethanoamine) at the 1,4-position, forming symmetrical cations with bromide, hexafluorophosphate and bis(trifluoromethanesulfonyl)imide as the counter-anions. Dicationic ionic liquids were successfully synthesized with yield of more than 85%, through conventional methods (quaternization reaction followed by anion exchange). Counter-anion plays an important role in determining thermal properties of dicationic ionic liquids. Bromide moieties have poorer thermal stability compared with hexafluorophosphate moieties. On the other hand, bis(trifluoromethanesulfonyl)imide moieties are the most thermally stable dicationic ionic liquids while having the lowest melting point. Few bis(trifluoromethanesulfonyl)imide salts melt at temperature below 100°C which is in good agreement with the definition of ionic liquids. All dicationic ionic liquids appear as solid at ambient temperature and were purified through recrystallization with an appropriate solvent. Upon recrystallization, nine dicationic ionic liquids afforded single crystal suitable for X-ray crystallography 3 measurement. The molecular structure of crystals are solved, refined, and found to be in good agreement with the expected structures. Based on the chromatographic analysis, hexafluorophosphate and bis(trifluoromethanesulfonyl)imide moieties have extremely low bromide and water content.